2021
DOI: 10.1002/eat.23553
|View full text |Cite
|
Sign up to set email alerts
|

The intersect of gastrointestinal symptoms and malnutrition associated with anorexia nervosa and avoidant/restrictive food intake disorder: Functional or pathophysiologic?—A systematic review

Abstract: Objective Although multiple pathophysiologic changes develop within the gastrointestinal (GI) system in the setting of malnutrition, the etiology of the reported multitude of symptoms in those with anorexia nervosa and avoidant restrictive intake disorder, as well as their contribution toward disordered eating, remain poorly understood. This systematic review seeks to better understand how these physiologic changes of malnutrition of the esophagus, stomach, intestines, and pancreas contribute toward the report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 151 publications
0
22
0
Order By: Relevance
“…Vettoretto et al (2010) reported that intraluminal gastric contents consisting of even 3 L can distend the stomach to an intraluminal pressure that impedes blood flow and increases risk for gastric necrosis and perforation. Given the high mortality associated with the complications of acute gastric dilatation (Gibson et al, 2021) and the baseline gastric dilatation suggested in this study, future research must better define, and thus differentiate, between the aforementioned acute gastric dilatation and the newly described potential association between enlarged gastric dimensions and malnutrition secondary to an ED; furthermore, future research must seek to understand the impact of the baseline gastric dilatation toward development of the more sinister complications associated with acute gastric dilatation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vettoretto et al (2010) reported that intraluminal gastric contents consisting of even 3 L can distend the stomach to an intraluminal pressure that impedes blood flow and increases risk for gastric necrosis and perforation. Given the high mortality associated with the complications of acute gastric dilatation (Gibson et al, 2021) and the baseline gastric dilatation suggested in this study, future research must better define, and thus differentiate, between the aforementioned acute gastric dilatation and the newly described potential association between enlarged gastric dimensions and malnutrition secondary to an ED; furthermore, future research must seek to understand the impact of the baseline gastric dilatation toward development of the more sinister complications associated with acute gastric dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the resting gastric dimension toward gastric accommodation and reported GI symptoms in this population requires further investigation. Indeed, reduced gastric accommodation and visceral hypersensitivity are suspected contributors to the symptoms in functional dyspepsia (Di Stefano et al, 2005; Simrén et al, 2018), and functional GI diseases (FGIDs) are highly prevalent in this ED population (Gibson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of routine assessment of GID within the dietetic treatment of AN offers the potential to improve treatment outcomes. Although the efficacy of current dietetic treatment for GID in AN have not been evaluated, malnutrition has a direct impact on the physiology of the GI tract, including altering motility [ 57 ]. Furthermore, engagement in ED behaviours, such as restriction and purging are directly related to GID presence [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…With growing awareness of this relationship, research has increasingly focused on identifying DGBIs among patients with EDs, with recent systematic reviews highlighting the most common symptoms [ 19 , 27 ]. More research is certainly needed on shared (e.g., genetic) risk factors for ED and DGBI development.…”
Section: Introduction: Disorders Of Gut–brain Interaction and Eating ...mentioning
confidence: 99%